2019
DOI: 10.1037/pap0000166
|View full text |Cite
|
Sign up to set email alerts
|

Does maternal reflective functioning mediate associations between representations of caregiving with maternal sensitivity in a high-risk sample?

Abstract: Although it is known that mothers with substance abuse disorders struggle to provide adequate parenting to their children, little is understood about the mechanisms behind this. This cross-sectional study uses an attachment perspective to examine whether reflective functioning mediates the relationship between mental representations of caregiving and maternal sensitivity, in an ethnically diverse sample of 142 substance-abusing mothers (M [SD] = 29.83 [5.79] years of age) and their toddlers (M [SD] = 24.04 [15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Maternal mentalisation has been found to be associated with the quality of maternal caregiving and infant attachment security and shown to be a protective factor in the intergenerational transmission of attachment (Grienenberger et al., 2005; Slade et al., 2005). Some studies using high‐risk samples have found that parenting sensitivity mediates the relationship between RF and infant attachment (Stacks et al., 2014) and that RF mediates the relationship between maternal representations and caregiving sensitivity (Alvarez‐Monjarás, McMahon, & Suchman, 2019). However, few studies have focused on maternal mentalisation in mothers with BPD features.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal mentalisation has been found to be associated with the quality of maternal caregiving and infant attachment security and shown to be a protective factor in the intergenerational transmission of attachment (Grienenberger et al., 2005; Slade et al., 2005). Some studies using high‐risk samples have found that parenting sensitivity mediates the relationship between RF and infant attachment (Stacks et al., 2014) and that RF mediates the relationship between maternal representations and caregiving sensitivity (Alvarez‐Monjarás, McMahon, & Suchman, 2019). However, few studies have focused on maternal mentalisation in mothers with BPD features.…”
Section: Introductionmentioning
confidence: 99%
“…While other studies have shown that mothers with SUDs tend to have more negative representations of their child and the parent-child relationship (Alvarez-Monjarás et al, 2019;Suchman et al, 2018), none have specifically examined profiles related to the three WMCI classifications. In this paper, the largest proportion of mothers in the OUD sample were classified as having disengaged representations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a sample of both psychiatric clinic-referred and nonreferred infants, mothers with representations characterized by higher levels of coherence and joy showed more sensitivity and less intrusiveness with their children, and also provided more support during a problem-solving task (Dollberg et al, 2010). Among mothers with substance use disorders (SUDs), those who had higher quality representations or showed improvement in representations over time demonstrated greater sensitivity with their young children (Alvarez-Monjarás et al, 2019;Suchman et al, 2018).…”
Section: Statement Of Relevance To the Field Of Infant And Early Childhood Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality (i.e., coherence, flexibility, and richness) of internal representations may also affect a mother’s capacity to make sense and adapt their own behavior to sensitively and appropriately respond to their child’s preverbal demands and mental states (Alvarez-Monjarás, McMahon, & Suchman, 2019; Fonagy, Gergely, & Target, 2007; Fonagy, Steele, Steele, Moran, & Higgitt, 1991). For instance, mothers with disengaged representations in the Adult Attachment Interview (George, Kaplan, & Main, 1985) tend to be less sensitive, more passive, and less encouraging, whereas those with more coherent representations engage in less negative (e.g., aggressive or intrusive) and more positive (e.g., warm or soothing) parenting practices (Slade, Belsky, Aber, & Phelps, 1999; Sokolowski, Hans, Bernstein, & Cox, 2007).…”
Section: Motherhood: a Normal Crisismentioning
confidence: 99%